Outcomes of percutaneous endoscopic gastrostomy tube placement using a T-fastener gastropexy device in head and neck and esophageal cancer patients - Chadha, Krishdeep Singh; Thatikonda, Chandana; Schiff, Michael; Nava, Hector; Sitrin, Michael D (Nutrition in clinical practice, 2010)
Percutaneous endoscopic gastrostomy (PEG) tube placement by the pull technique in head, neck, and esophageal cancer patients has a high complication rate, particularly in infections, and a small risk of tumor implantation. The T-fastener gastropexy technique uses a transabdominal approach to place the PEG device. The objective of this study was to review the clinical outcomes and complications related to endoscopic PEG placement with the T-fastener gastropexy technique in patients with head, neck, and esophageal cancers. This study was a retrospective review of all patients with head, neck, and esophageal cancers with PEG placement from January 1998 to June 2008. Clinical data including patient's age, gender, type and stage of cancer, date of PEG placement and removal, and reason for PEG removal was recorded. The study group consisted of a total of 356 patients of which 244 were male and 112 were female with a mean age of 63.3 years. There were 276 patients with head and neck cancer, 75 patients with esophageal cancer, and 5 with gastro-esophageal junction cancer. Staging data was available for 326 patients of which 56 (17.1%) had early stage disease (stage 1 and 2) and 270 patients (82.9%) had late stage (3 and 4) disease. None of these patients received antibiotic prophylaxis prior to PEG placement. Cellulitis around the PEG site occurred in 8.4% of cases and an abscess in 3.7% of cases. Only 4 (1.2%) infectious complications were within the first 30 days of PEG placement, and there were no intraoperative deaths or cases of tumor implantation. In the authors' experience, the T-fastener gastropexy technique for PEG placement in head, neck, and esophageal cancer patients carried a low overall complication rate and compared favorably with the results of pull method reported in the literature.